2017
DOI: 10.14710/jitaa.42.4.213-219
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism of kappa-casein gene in Friesian Holstein: a basic selection of dairy cattle superiority

Abstract: ABSTRAKKasein adalah protein susu yang terbagi dalam empat grup yaitu αS1, αS2, β-casein dan kappacasein (CSN3). Gen kappa-kasein berpengaruh terhadap pembentukan komponen dalam susu. Tujuan dari penelitian adalah mengidentifikasi polimorfisme gen kappa-kasein pada sapi perah Friesian Holstein (FH). Sebanyak 59 sampel sapi FH yaitu 32 asal Malang, 10 asal Sukahati Bogor dan 17 asal Pusat Penelitian Bioteknologi-Lembaga Ilmu Pengetahuan Indonesia (LIPI) (ternak koleksi) digunakan dalam penelitian. Sampel DNA di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…For high productive Holstein Friesian breed some authors (Volkandari et al, 2017, Tanaskovska et al, 2016, Khaizaran and Razem, 2014, Dokso et al, 2014, Ren et al, 2011 determined higher frequency of AA genotype than AB and BB genotypes, what is similar to result obtained for Brown Swiss breed. Other authors, as Doosti et al (2011), Gouda et al (2013), Maletić et al (2016) reported for Holstein breed the highest frequency of AB genotype κ-casein.…”
Section: Resultssupporting
confidence: 63%
“…For high productive Holstein Friesian breed some authors (Volkandari et al, 2017, Tanaskovska et al, 2016, Khaizaran and Razem, 2014, Dokso et al, 2014, Ren et al, 2011 determined higher frequency of AA genotype than AB and BB genotypes, what is similar to result obtained for Brown Swiss breed. Other authors, as Doosti et al (2011), Gouda et al (2013), Maletić et al (2016) reported for Holstein breed the highest frequency of AB genotype κ-casein.…”
Section: Resultssupporting
confidence: 63%
“…Zyiad & Fawzi (2014) reported that A and B genotypes were favorable alleles in Palestinian Holstein-Friesian cattle. Similarly, some researchers found that A allele in Holstein-Friesian was as dominant allele in milk protein genes (Volkandari et al 2017;Barbosa et al 2019;Huang et al 2012).…”
Section: Genetic Variants Of Milk Protein Genesmentioning
confidence: 94%
“…In this study, it was known that the A allele dominant at the milk protein genes. Volkandari et al (2017) stated that polymorphic which AA genotypes and A allele at locus κ-casein were frequently commonly found in Holstein Friesian cattle. Zyiad & Fawzi (2014) reported that A and B genotypes were favorable alleles in Palestinian Holstein-Friesian cattle.…”
Section: Genetic Variants Of Milk Protein Genesmentioning
confidence: 99%
“…Nowadays, the study of milk productivity of cows associated with alleles or genotypes of specific genes responsible for the productive properties of cattle is topical and relevant. This will allow us to predict the lifetime milk productivity of cows, the quality of dairy products, to improve the selection work at large-scale dairy units (Volkandari et al, 2017;Barbosa et al, 2019;Ladyka et al, 2021). In addition, this work should confirm or refute the hypothesis that a certain genotype of the kappa-casein gene in the breed Swiss cows is associated with certain economically useful traits, such as high milk yields or protein and fat content.…”
Section: Introductionmentioning
confidence: 99%